"LOREH" Modifikasi Lotion Minyak Sereh Anti Nyamuk Berbasis Pendekatan Kelompok Berisiko Eliminasi Malaria di Balai Desa Ngemplak, Pagerharjo, Samigaluh, Kulon Progo - Kasjono Heru Subaris; Rosyida Putri, Haqifa (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2023)
The only district in Yogyakarta that experiences fluctuations in malaria cases is Kulon Progo district. Based on the data table on morbidity and mortality due to malaria according to gender, it refers to the Samigaluh II Community Health Center with a positive number of exposure of 8 people in 2021. In June 2015, the Samigaluh II Community Health Center created a policy in the form of a Community Health Center SMS Center. The aim is to improve reactions that are quickly identified, quickly discovered, and quickly treated so that local transmission will not occur. Even though it was successful, this policy did not last long. It can be seen that in 2017 the number of malaria cases in this village increased again. Therefore, the public wants a movement or solution action from the government regarding this problem. In order to support the community's wishes, we held a direct observation movement to Ngemplak Hamlet, Pagerharjo, Samigaluh, Kulon Progo, Special Region of Yogyakarta. This movement is called 3P (Extension, Independent Creation, and Mentoring). The main target is aimed at PKK mothers and Karang Taruna in each hamlet. The 3P movement began with malaria education outreach, independent production of "LOREH" lemongrass oil lotion and systematic assistance. This activity requires collaboration with health workers and local health centers so that they can monitor better. The output of the 3P movement is an increase in understanding, attitudes and environmentally